2020
DOI: 10.3390/cryst10090767
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Modeling Simulator for Near-Field Processes in Cement Engineered Barrier Systems for Radioactive Waste Disposal

Abstract: Details are presented of the development of a coupled modeling simulator for assessing the evolution in the near-field of a geological repository for radioactive waste disposal where concrete is used as a backfill. The simulator uses OpenMI, a standard for exchanging data between simulation software programs at run-time, to form a coupled chemical-mechanical-hydrogeological model of the system. The approach combines a tunnel scale stress analysis finite element model, a discrete element model for accurately mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In developing a new analytical approach, Benbow et al (2020) demonstrated that coupling of non-linear processes could be achieved by coupling of the computer programs MACBECE (JAEA 2018;Ohno et al 2009;Mihara et al 2017), DEAFRAP (JAEA 2018; Shimizu et al 2011) and GARFIELD-CHEM (Benbow et al 2020) as shown schematically in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In developing a new analytical approach, Benbow et al (2020) demonstrated that coupling of non-linear processes could be achieved by coupling of the computer programs MACBECE (JAEA 2018;Ohno et al 2009;Mihara et al 2017), DEAFRAP (JAEA 2018; Shimizu et al 2011) and GARFIELD-CHEM (Benbow et al 2020) as shown schematically in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…For equilibrium reactions, "grid convergence' is not possible with continuum scale numerical methods . For consideration of kinetic reactions, discretization on the mm scale has been identified as a necessary requirement for the numerical solution to agree with the analytical solution , whereas discretization on the cm scale is generally used in long-term reactive-transport simulations to save computation time (Benbow et al 2020;Trotignon et al 2007;Mon et al 2017). Previous experimental studies, for example, those by Sarott et al (1992), Pfingsten (2001) and , have found that thin surface layers of calcite can significantly reduce cement reactivity and mass transport properties due to pore-clogging at the outer cement surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the admixtures, erosion age, concentration of sulfate solution, and sulfate erosion on the mechanical properties of mortar were investigated by Liu et al [11]. Benbow et al [12] presented the development of a coupled modeling simulator for assessing the evolution of a geological repository in the near field for radioactive waste disposal where concrete is used as backfill.…”
mentioning
confidence: 99%